1996
DOI: 10.1007/bf01955189
|View full text |Cite
|
Sign up to set email alerts
|

Hypozincaemia in febrile convulsion

Abstract: Serum and CSF Zn levels are decreased in children with febrile seizures. Zinc deprivation may play a role in the pathogenesis of febrile seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 10 publications
7
48
0
1
Order By: Relevance
“…Mahyar et al and few other researchers have also reported similar findings in their studies suggesting that no specific age group or gender is particularly predisposed to develop hypozincemia. [16][17][18][19][20] A significant difference of 10.46 µg/dl in the mean serum zinc levels in cases(lower) compared to controls was also noted in the present study. The findings are consistent with some previous studies.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Mahyar et al and few other researchers have also reported similar findings in their studies suggesting that no specific age group or gender is particularly predisposed to develop hypozincemia. [16][17][18][19][20] A significant difference of 10.46 µg/dl in the mean serum zinc levels in cases(lower) compared to controls was also noted in the present study. The findings are consistent with some previous studies.…”
Section: Discussionsupporting
confidence: 73%
“…The findings are consistent with some previous studies. 5,[9][10][11][12][13]19,20 Hypozincemia in present study was found to be more prevalent in children with simple febrile seizures compared to the control group. However, no classical clinical manifestations of hypozincemia like diarrhoea, impaired appetite, decreased growth velocity, acroorificial skin lesions, delayed wound healing, dysguesia and hypoguesia were present in these patients, demonstrating purely biochemical hypozincemia.…”
Section: Discussionmentioning
confidence: 70%
“…However, FS represents the point between a low seizure threshold and genetic components, recognized to be susceptible for FS and caused by mutations in several gene maps, such as FEB-1 to FEB-4 (5-7). Moreover, some mutations causing neural hyperexcitability could be responsible for FS especially with polygenic multifactorial genetic trait (5,6,8).…”
mentioning
confidence: 99%
“…In the case group, zinc levels were found to be significantly lower than those in other groups. Further, in other studies, mean serum zinc levels were found to be lower in patients with FC (27,28). Salehiomran and Mahzari (29) reported that the mean serum zinc level was 0.585±0.166 mg/L and 0.704±0.179 mg/L in the case and control groups, respectively.…”
Section: Casementioning
confidence: 77%